The Efficiency of Sclerotherapy for the Management of Endometrioma: A Systematic Review and Meta-Analysis of Clinical and Fertility Outcomes - Carlo Ronsini; Irene Iavarone; Eleonora Braca; Maria Giovanna Vastarella; Pasquale De Franciscis; Marco Torella (Medicina, 2023)
Background and Objectives: The most common sites of implantation of endometriotic tissue are the ovaries. Endometriomas are present in most cases of endometriosis (up to 45%). Although laparoscopic cystectomy is the standard of care in endometrioma, new strategies have been set up to minimize iatrogenic injuries to ovarian tissue. Sclerotherapy consists of injecting alcohol into the endometrioma to denature the amino acidic components of its pseudocapsule. The aim of this systematic review and meta-analysis is to compare clinical and pregnancy outcomes in surgery and sclerotherapy. Materials and Methods: Following the recommendations in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement, we systematically searched PubMed, EMBASE, Scopus, Google Scholar, Clinical-trials.gov, and the Cochrane Central Register of Controlled Trials databases in January 2023, adopting the string “Endometriosis and sclerotherapy”. We made no limitations on the country and year of publication. We included the studies containing Success Rate (SR), Recurrence Rate (RR), Pregnancy Rate (PR) before and after the procedure. We used comparative studies for meta-analysis. Results: A total of 29 studies fulfilled inclusion criteria, 7 retrospective observational studies and 22 prospective studies. Eight comparative studies were enrolled in meta-analysis. Patients were analyzed concerning the number of recurrences and pregnancies in surgery, and compared with sclerotherapy. Four studies showed SR > 80.0%, and only two had SR < 80.0%, of which one consisted of tetracycline instillation. Only 1 study had 100% PR, the other 14 reported PR > 30.0%, whereas six had PR < 30.0%, of which one showed 0.0% PR with ethanol injection at two-thirds of the cyst fluid volume. Meta-analysis highlighted a non-significant lower incidence of recurrence in the surgery group compared to the sclerotherapy group (p = 0.87). In parallel, the surgery group showed a non-significant better PR than the sclerotherapy group (p = 0.08). Conclusions: Despite sclerotherapy having a minor incidence of postoperative complications compared to surgery, the latter is associated with a lower RR and better PR. However, those data assert the importance of a targeted therapy according to preoperative conditions and reproductive potential.